Penerapan PBL Ecological Awareness pada Materi Geografi SMA Negeri 1 Kuala Kurun - Binana Naz Srulin; Chatarina Muryani; Sugiyanto Sugiyanto (Universitas Negeri Medan, 2026)
This study investigates the effectiveness of Ecological Awareness-based Problem-Based Learning (PBL) in enhancing students' problem-solving skills in secondary geography education. The research was motivated by the limited integration of sustainability-oriented learning and ecological awareness within conventional geography classrooms, which remain predominantly teacher-centered. A Classroom Action Research (CAR) design consisting of three iterative cycles was implemented involving 35 eleventh-grade students at SMA Negeri 1 Kuala Kurun during the 2024/2025 academic year. Data were collected through classroom observations, problem-solving tests, questionnaires, reflective journals, and field notes. Quantitative data were analyzed using descriptive statistics, normalized gain (N-gain), and effect size, while qualitative data were examined using thematic analysis. The findings demonstrate a consistent improvement in students' problem-solving abilities and learning outcomes across the three cycles. Learning mastery increased from 68.6% in Cycle I to 91.4% in Cycle III, while the average written test score improved from 63.85 to 86.85. The N-gain score of 0.64 indicates a high level of improvement, and the effect size of 1.12 reflects a strong instructional impact. Furthermore, the integration of ecological awareness into each stage of PBL fostered students' critical thinking, sustainability-oriented reasoning, and engagement with real-world environmental issues. These findings suggest that Ecological Awareness-based PBL provides an effective pedagogical framework for promoting meaningful, contextual, and sustainability-oriented geography learning.